Strategi Kepala Sekolah Dalam Menciptakan Budaya Religius di SMK Negeri 1 Samarinda - Mustapa, Akhmad; Nurbayani, Etty; Nasiah, Siti (el Buhuth: Borneo Journal of Islamic Studies, 2019)
SMK Negeri 1 Samarinda (State Vocational High school 1 of Samarinda) is a general school that the principal still wants to build the Islamic character values through the 3S culture (Smile, Respect, and Greet), the culture of reading the holy Qur’an, praying together, the culture of discipline and honesty, and ethics in clothing. This research aims to find out the religious culture at SMK Negeri 1 Samarinda. The approach used was qualitative approach with qualitative descriptive research type. The data collection techniques were observation, interviews and documentation. Data validity test used source and method triangulation analyzed with member check. The data analysis technique used data reduction, presentation and concluding. The result of the research is that religious activities developed by the principal are such as the culture of 3S, reading Qur’an, praying before and after learning, praying together at the school mosque, the culture of honesty, discipline and ethics in clothing. The strategies of the principal in creating the religious culture at SMK Negeri 1 Samarinda were through planning, modelling, habituation, participation, evaluation, coordination, and motivation.